2000
DOI: 10.1103/physrevlett.85.5651
|View full text |Cite
|
Sign up to set email alerts
|

DNA Electrophoresis on a Flat Surface

Abstract: We report a new approach for performing DNA electrophoresis. Using experimental studies and molecular dynamics simulations, we show that a perfectly flat silicon wafer, without any surface features, can be used to fractionate DNA in free solution. We determine that the ability of a flat surface to separate DNA molecules results from the local friction between the surface and the adsorbed DNA segments. We control this friction by coating the Si surface with silane monolayer films and show that it is possible to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
85
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(90 citation statements)
references
References 25 publications
4
85
1
Order By: Relevance
“…Pernodet and co-workers [29] recently proposed and tested a novel method for the separation of DNA fragments based on the strikingly simple process of inducing electrophoretic migration near a smooth surface. Using this approach, DNA strands migrate across a planar sub- Figure 1.…”
Section: Surface Electrophoresismentioning
confidence: 99%
See 1 more Smart Citation
“…Pernodet and co-workers [29] recently proposed and tested a novel method for the separation of DNA fragments based on the strikingly simple process of inducing electrophoretic migration near a smooth surface. Using this approach, DNA strands migrate across a planar sub- Figure 1.…”
Section: Surface Electrophoresismentioning
confidence: 99%
“…In order to better understand the separation mechanisms at work in surface electrophoresis, Luo and Gersappe [29,31] performed Brownian Dynamics simulations of adsorbed chains subjected to a low intensity electric field. They used a standard coarse-grained approach in which all monomers interact via a Lennard-Jones (LJ) potential while adjacent ones interact via a finitely-extensible nonlinear elastic (FENE) potential [32].…”
Section: Surface Electrophoresismentioning
confidence: 99%
“…The development of accurate and versatile DNA separation technique is currently a significant issue in nanobiotechnology. 1 Recently, Pernodet et al 2 reported separation of DNA chains on a surface without any topological restrictions or any solution sieving media. This can be a significant benefit over conventional separation methods.…”
mentioning
confidence: 99%
“…By the process of changing the surface energy of a flat surface, it is possible to change the size range of DNA that can be separated by this method. Molecular dynamics (MD) simulation [12] confirms the separation of DNA molecules by modifying the interaction between the DNA and substrate surface.…”
Section: Introductionmentioning
confidence: 93%
“…A possible new approach to performing electrophoresis is to utilize the effect of surface interactions. In our recent work [12][13][14] it has been shown that the local friction between a fully absorbed DNA molecule and a flat homogeneous surface can result in the separation of long DNA fragment. In this approach the friction between the adsorbed segments and the surface is controlled by coating the surface with well controlled silane monolayer films.…”
Section: Introductionmentioning
confidence: 99%